2007
DOI: 10.1007/s00464-006-9142-3
|View full text |Cite
|
Sign up to set email alerts
|

Fixity of ports to the abdominal wall during laparoscopic surgery: a randomized comparison of cutting versus blunt trocars

Abstract: Port fixity to the abdominal wall during laparoscopic surgery declines with time. The insertion of ports using a blunt-tipped trocar is associated with significantly greater stability and fixity of the port to the abdominal wall. The use of blunt-tipped trocars is recommended for routine practice in laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The use of the bladeless blunttip trocar separates muscle and fascia rather than cutting it, which may help prevent trocar site hernia and abdominal wall vascular injury. [21][22][23] In our study, no patient had a trocar-site hernia identified during the follow-up period, and no patient developed bleeding at a DTI port site. Berch et al 13 also reported the same using the optical access trocar without a previous pneumoperitoneum in 327 obese patients.…”
Section: Discussionmentioning
confidence: 85%
“…The use of the bladeless blunttip trocar separates muscle and fascia rather than cutting it, which may help prevent trocar site hernia and abdominal wall vascular injury. [21][22][23] In our study, no patient had a trocar-site hernia identified during the follow-up period, and no patient developed bleeding at a DTI port site. Berch et al 13 also reported the same using the optical access trocar without a previous pneumoperitoneum in 327 obese patients.…”
Section: Discussionmentioning
confidence: 85%
“…During laparoscopic procedures, the port site may become loose and dislodge the trocar from the abdominal wall, causing gas leakage, hypothermia, and frequent trocar displacement. The problem is more common with cutting‐edge trocars . When the abdominal cavity is entered using an open technique, an inadvertently wide fascial incision may cause problems from the beginning of procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that blunt-tipped conical port instruments have a significantly greater fixity to the abdominal wall compared to cutting port instruments, resulting in significantly lower numbers of spontaneous port dislodgement during surgery [14]. Accordingly, the use of blunt-tipped instruments could reduce antecedent gas leak and loss of pneumoperitoneum and the need for port replacement with its associated increase in risk of trauma to the abdominal wall.…”
Section: Considerationsmentioning
confidence: 96%
“…In four, REA instruments were compared with standard port instruments for primary port entry [10][11][12][13]. Two RCTs compared cutting and blunt port instruments for primary and secondary port entry [14,15], and in two RCTs, the REA instrument was compared to a conventional instrument with cutting tip for secondary port entry [16,17]. Trials that analyzed major complications with low incidences had too small sample sizes to identify any differences [10,12,[15][16][17].…”
Section: Major Port-related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation